Buletin Peternakan : Penurunan Total Tanin Silase Semak Bunga Putih (Chromolaena odorata) dengan Aditif Tepung Putak (Coryphaelata robx) dan Isi Rumen Sapi - muhammad ridla, Yelly Magdalena Mulik, Iwan Prihantoro, Marthen Luther Mullik (Peternakan UGM, 2016)
his study was aimed to assess the effect of the addition of putak meal (as a source of carbohydrates) and rumen content (as a source of enzymes) in the making of C. odorata silage to the total content of tannins and nutrient content of C. odorata silage.